2017
DOI: 10.1007/978-3-319-60525-8_44
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Assessment Tool for Real-Time Risk Assessment of Seated Work Postures

Abstract: et al. (2 more authors) (2018) Ergonomic assessment tool for real-time risk assessment of seated work postures.Abstract. This paper presents a posture assessment tool which utilizes the depth sensing techniques of a 3D imaging sensor for ergonomic risk assessment of seated worker's postures during controlled manual handling tasks. The tool, which has been developed to utilize the manual handling guidelines by the Health and Safety Regulators of some selected countries to measure and assess the postures of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Outro agravante é o fato de que conforme os quadris giram, maior pressão é aplicada na coluna quando o tronco é dobrado para a frente, causando dores nas costas e lesões. Portanto, manter uma boa postura sentada durante o trabalho não só melhora a eficiência, mas também protege a saúde do trabalhador (Mgemena et al, 2017).…”
Section: Resultsunclassified
“…Outro agravante é o fato de que conforme os quadris giram, maior pressão é aplicada na coluna quando o tronco é dobrado para a frente, causando dores nas costas e lesões. Portanto, manter uma boa postura sentada durante o trabalho não só melhora a eficiência, mas também protege a saúde do trabalhador (Mgemena et al, 2017).…”
Section: Resultsunclassified
“…RULA analysis from the observation results showed that 43.20% of scavengers had a score of 7, indicating a change in posture should be done immediately.Meanwhile, 45.5% of scavengers got a score of 5, indicating that changes in posture must be carried out immediately. The chi-square analysis showed a significant relationship between the neck and low back pain prevalence with an identified risk level at p<0.05 [25]. Complaints of musculoskeletal disorders are thought to be influenced by nonergonomic work postures, according to the REBA method assessment of the factors that cause complaints of musculoskeletal disorders, including long working time, loading, frequency, and handgrip [26].…”
Section: Complaintsmentioning
confidence: 99%
“…A photogrammetric analysis method was used by (Naddeo et al, 2015) to measure joint angles of the Neck, shoulders, elbow and wrists for comfort evaluation of upper extremities of the human body. Microsoft Kinect has been recommended as an alternative method for risk assessment because of its low cost and 3D motion capture capabilities (Diego-Mas and Alcaide-Marzal, 2014;Dutta, 2012;Ho et al, 2016;Mgbemena et al, 2018Mgbemena et al, , 2017Mgbemena et al, , 2016Rosário, 2014).…”
Section: Ergonomic Risk Assessment Toolsmentioning
confidence: 99%